Jewish Theological Seminary of America Library. Broadside Collection. Hamden, Conn.: Micrographic Systems of Connecticut for The Jewish Theological Seminary of America, 1992. 3 microfilm reels. 35.00 per reel + shipping - Walfish, Barry (Judaica Librarianship, 1995)
Reviews the broadside collection published by the Jewish Theological Seminary on microfilm, provides highlights from the collection, and evaluates the organization, cataloging, and indexing of the material.